2018
DOI: 10.7554/elife.37168
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic ATF6 activating compounds are metabolically activated to selectively modify endoplasmic reticulum proteins

Abstract: Pharmacologic arm-selective unfolded protein response (UPR) signaling pathway activation is emerging as a promising strategy to ameliorate imbalances in endoplasmic reticulum (ER) proteostasis implicated in diverse diseases. The small molecule N-(2-hydroxy-5-methylphenyl)-3-phenylpropanamide (147) was previously identified (Plate et al., 2016) to preferentially activate the ATF6 arm of the UPR, promoting protective remodeling of the ER proteostasis network. Here we show that 147-dependent ATF6 activation requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
167
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(181 citation statements)
references
References 55 publications
(107 reference statements)
14
167
0
Order By: Relevance
“…Prior work showed that 147 is a prodrug that is metabolically oxidized to an iminoquinone or quinone methide, which covalently targets nucleophilic cysteine residues on cellular protein (Palmer et al, 2020;Paxman et al, 2018;Plate et al, 2016). We showed that the antiviral activity of 147 could be attenuated with BME treatment, demonstrating that the metabolic activation mechanism and covalent targeting of reactive thiols is similarly required to reduce virus infection.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Prior work showed that 147 is a prodrug that is metabolically oxidized to an iminoquinone or quinone methide, which covalently targets nucleophilic cysteine residues on cellular protein (Palmer et al, 2020;Paxman et al, 2018;Plate et al, 2016). We showed that the antiviral activity of 147 could be attenuated with BME treatment, demonstrating that the metabolic activation mechanism and covalent targeting of reactive thiols is similarly required to reduce virus infection.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies showed that 147 is a prodrug and requires metabolic activation in cells to generate a reactive p-quinone methide that can then form protein adducts with reactive cysteine residues ( Fig. 4A) (Palmer et al, 2020;Paxman et al, 2018;Plate et al, 2016). In several cell types, ER-resident protein disulfide isomerases (PDIs) were identified as the common protein targets of 147, and this modulation of PDIs was linked to the activation of ATF6 .…”
Section: Reduced Denv Propagation Requires 147 To Covalently Target Pmentioning
confidence: 99%
“…An inhibitor of S1P, the Golgi protease that cleaves and activates ATF6, inhibited 147-mediated ATF6 target gene induction. Using "click" chemistry and forms of 147 with chemical handles, the 147 interactome was defined in an attempt to demonstrate the mechanism by which it activates ATF6 [129]. It was discovered that 147 binds PDIs, which regulate disulfide bond formation in the ER.…”
Section: Small Molecule Atf6-activators Confer Protection Against Carmentioning
confidence: 99%
“…The activation of ATF6 by 147 can be inhibited by co-administration of resveratrol or β-mercaptoethanol 99 (BME), which block different steps of the compound activation mechanism ( Figure 4A) (Paxman et al, 2018). 00…”
Section: Reduces Allc Secretion Through An On-target Mechanism Involvmentioning
confidence: 99%
“…One of the most promising small 85 molecules emerging from this screen was compound 147. Using a combination of medicinal chemistry and 86 chemical biology, we showed that 147 activates ATF6 through a mechanism involving compound metabolic 87 activation and covalent labeling of multiple PDIs (Paxman et al, 2018). Since PDIs are involved in regulating 88 the proper folding and disulfide bond formation for ER-targeted proteins (Appenzeller-Herzog & Ellgaard, 2008, 89…”
mentioning
confidence: 99%